The slope of the source-count distribution for fast radio bursts. Issue 1 (10th November 2018) - James, C W; Ekers, R D; Macquart, J-P; Bannister, K W; Shannon, R M
ABSTRACT: The slope of the source-count distribution of fast radio burst (FRB) fluences, α, has been estimated using a variety of methods. Hampering all attempts have been the low number of detected FRBs, and the difficulty of defining a completeness threshold for FRB surveys. In this work, we extend maximum likelihood methods for estimating α, using detected and threshold signal-to-noise ratios applied to all FRBs in a sample without regard to a completeness threshold. Using this method with FRBs detected by the Parkes radio telescope, we find α = −1.18 ± 0.24 (68 per cent confidence interval, CI), i.e. consistent with a non-evolving Euclidean distribution (α = −1.5). Applying these methods to the Australian Square Kilometre Array Pathfinder (ASKAP) Commensal Real-time ASKAP Fast Transients (CRAFT) FRB survey finds α = −2.2 ± 0.47 (68 per cent CI). A full maximum likelihood estimate finds an inconsistency with the Parkes rate with a p -value of 0.86 per cent (2.6σ). If not due to statistical fluctuations or biases in Parkes data, this is the first evidence for deviations from a pure power law in the integral source-count distribution of FRBs. It is consistent with a steepening of the integral source-count distribution in the fluence range 5–40 Jy ms, for instance due to a cosmological population of FRB progenitors evolving more rapidly than the star formation rate, and peaking in the redshift range 1–3.